Paisagem como ligação entre a conservação do patrimônio e o planejamento territorial: conservation-preservation through development - Laura Beatriz Lage (2018)
From the perception of the transformations occurring in everyday landscapes without concern to the pre-existing, losing environmental and aesthetic quality, as a consequence of the dichotomy existed between the two knowledge fields that deal with transformations and permanencies in space: heritage preservation and urban and territorial planning, established by the paradigm of modern science, which contributes to creation of spaces without stimmung, making the trajectiva between the subject and the object impossible, where landscape comes from, this work starts from the hypothesis that the concept of landscape, as addressed by the European Landscape Convention (ELC), can restore the connection between man and the environment, allowing the integration of disciplinary approaches considered discordant and enabling a protection/conservation through development. The discomfort with the transformation of landscapes and the substitution of its elements for others that have no relation with the place was found in ELC, is also expressed in the Belvedere Memorandum, Dutch territorial management plan (1999-2009), and due to the strong connection of people with their territory, were developed methodologies to identify the character of their landscapes to guide future developments, as in the case of Historic Landscape Characterisation (HLC) in England. This work addresses these concerns and methodologies, using a broad concept of landscape, avoiding its simplification and consequent impoverishment of the concept due to its categorisation.